THE INFLUENCE OF PMDN, PMA AND GOVERNMENT SPENDING ON UNEMPLOYMENT IN REGENCIES/CITIES OF WEST KALIMANTAN 2008 - 20013 - B01111055, RINA MUTIA SARI (Jurnal Pembangunan dan Pemerataan, 2015)
This research aimed to examine the of PMDN (Domestic Investment), PMA (Foreign Investmen) and Government Spending against unemployment in Regencies/Cities of West Kalimantan in the period of 2008 - 2013. This study falls into the category of quantitative research which, in addition to descriptive research, also describes the development of the unemployment rate for six years in Regeincies/Cities of West Kalimantan using explanatoryresearh. The data was processed test method using Eviews 6. The results of the data processing showed that the variables of foreign investmnet (PMA) and Government Spending simustaneously had a significant influence on unemployment in 11 Regencies/Cities of West Kalimantan, Regencies/Cities of West Kalimantan, but Domestic Investment (PMDN) is not significant influence on unemployment in 11 Regencies/Cities of West Kalimantan, Regencies/Cities of West Kalimantan.The research findings showed that PMDN (Domestic Investment) had a posittive influence at 0.1472 and was not significant, whereas PMA (Foreign Investmen) had a negative influence at 0.0008 and was significant; Government Spending had a negative influence at 0.0068 and significant on unemployment in 11 Regencies/Cities of West Kalimantan. The coefficient of detrmination value (R2) was 0.914895, meaning that the variables od domestic investment, foreign investment, and government spending had an influence on unemployment in 11 Regencies/Cities of West Kalimantan by 91 %, while the remaning 9 % was influenced by other factor.Keywords : Unemployment, PMDN (Domestic Investment), PMA (Foreign Investmen) and Government Spending